Visitors’ brand awareness toward Pohsanten Tourist Village - Arjana, I Wayan Basi; Ernawati, Ni Made; I Putu Budiarta; Voda , Mihai (Politeknik Negeri Bali, 2022)
This study is to determine the level of brand awareness of visitors consisting of top of mind, brand recall, brand recognition and unaware of brand at Pohsanten Tourist Village in Jembrana Regency, Bali, Indonesia. Data were collected by using a questionnaire distributed to visitors to the tourist village of Pohsanten using accidental compenience sampling to 60 respondents. The collected data were analyzed descriptively and quantitatively with frequency. From the results of the analysis it can be concluded that the Pohsanten Tourist Village have reached the Top of Mind in the minds of the respondents. This means that the Pohsanten Tourist Village brand is quite popular in the minds of visitors as one of the tourist villages in Jembrana Regency.